Understanding Growth-Induced Trends in Local Climate Zones, Land Surface Temperature, and Extreme Temperature Events in a Rapidly Growing City: A Case of Bulawayo Metropolitan City in Zimbabwe - Mushore, Terence Darlington; Mutanga, Onisimo; Odindi, John (Frontiers in Environmental Science, 2022)
Assessment of the responses of the urban thermal environment to climate is important, especially because of their possible influence on low- and high-temperature extreme events. This study assessed the combination of remotely sensed land surface temperature (LST) and local climate zones (LCZs) with in situ air temperature-retrieved extreme temperature indices. It aimed to assess the effect of urban growth on the three-dimensional thermal environment in the Bulawayo metropolitan area, Zimbabwe. LST and LCZ were derived from the Landsat data for 1990, 2005, and 2020, while extreme temperature indices and trends were derived from daily minimum and maximum temperature data from a local weather station. Results showed that the built LCZ expanded at the expense of vegetation-based LCZ. Average LST for each LCZ increased from 1990 to 2020, which was attributed to background warming, while the expansion of high LST areas was associated with LCZ transitions. Although average minimum temperature decreased, cool nights increased, warmest nights remained unchanged, and the lowest minimum increased, the highest minimum temperatures decreased, but the trends were not statistically significant (p > 0.05). Indices of daytime warming showed significant changes, which includes an increase in average maximum temperature (p = 0.002), increase in lowest maximum temperature (p = 0), increase in the number of very warm days (p = 0.004), and decrease in the number of cool days (p = 0). The significant increase in daytime extremes was attributed to an increase in highly absorbing LCZ and daytime pollution due to industrial activities. The study also concluded that development in water areas or siltation of water bodies has a greater warming effect than other LCZ changes. The findings show that development needs to consider potential effects on the thermal environment and temperature extremes.